2015
DOI: 10.1016/j.enconman.2015.07.047
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation on the influence of piston bowl geometry on RCCI performance and emissions in a heavy-duty engine

Abstract: This experimental work investigates the effects of piston bowl geometry on RCCI performance and emissions at low, medium and high engine loads. For this purpose three different piston bowl geometries with compression ratio 14.4:1 have been evaluated using single and double injection strategies. The experiments were conducted in a heavy-duty single-cylinder engine adapted for dual fuel operation. All the tests were carried out at 1200 rev/min.Results suggest that piston geometry has great impact on combustion d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 43 publications
(40 reference statements)
2
32
0
Order By: Relevance
“…Some other geometries aimed at reducing the heat transfer losses were also tested [23], confirming that the best strategy to increase the efficiency of RCCI concept is by reducing the in-cylinder area-to-volume ratio [24]. However, these studies showed that an excessive shallow bowl combined with single injection strategies can result in unacceptable soot emissions when trying to extend the RCCI concept up to high loads [25].…”
Section: Introductionmentioning
confidence: 82%
“…Some other geometries aimed at reducing the heat transfer losses were also tested [23], confirming that the best strategy to increase the efficiency of RCCI concept is by reducing the in-cylinder area-to-volume ratio [24]. However, these studies showed that an excessive shallow bowl combined with single injection strategies can result in unacceptable soot emissions when trying to extend the RCCI concept up to high loads [25].…”
Section: Introductionmentioning
confidence: 82%
“…include fuel ratio [14], injection strategy [15][16][17][18], EGR rate [19], compression ratio [16], bowl geometry [20,21], stability control, and utilization of two injectors.…”
Section: Improvement Trends For Internal Combustion Enginesmentioning
confidence: 99%
“…It has a port injector for low reactive fuel (LRF) and a direct injector for high reactive fuel (HRF) [14,51,56,[62][63][64][65][66]. Figure 5 shows the experimental setup for RCCI with port and direct injection (Dual fuel).…”
Section: Rcci With a Port And A Direct Injection (Dual Fuel)mentioning
confidence: 99%